Le ricerche scientifiche durante l’emergenza sanitaria (il CoViD-19). Quale base giuridica per l’arruolamento dei pazienti? (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The paper analyzes the difficult role of the right to privacy in the field of medical, biomedical and epidemiological research, in case of a National health emergency. Therefore, it will be assessed whether and how it is essential to obtain informed consent from patients in order to participate in clinical studies related to the CoViD-19 emergency.
Keywords: CoViD-19; pandemic emergency; research; privacy; informed consent